Dietary quercetin supplementation in mice increases skeletal muscle PGC1α expression, improves mitochondrial function and attenuates insulin resistance in a time-specific manner. - Tara M Henagan; Natalie R Lenard; Thomas W Gettys; Laura K Stewart (PLoS ONE, 2014)
Aims/hypothesis High fat diet (HFD)-induced insulin resistance (IR) is partially characterized by reduced skeletal muscle mitochondrial function and peroxisome proliferator activated receptor gamma coactivator 1 alpha (PGC1α) expression. Our previous study showed that a high dose of the bioflavonoid quercetin exacerbated HFD-induced IR; yet, others have demonstrated that quercetin improves insulin sensitivity. The aim of this study was to investigate whether differing doses of quercetin act in a time-dependent manner to attenuate HFD-induced IR in association with improved skeletal muscle mitochondrial function and PGC1α expression. Methods C57BL/6J mice were fed HFD for 3 or 8 wks, with or without a low (50 ug/day; HF+50Q) or high (600 ug/day, HF+600Q) dose of quercetin. Whole body and metabolic phenotypes and insulin sensitivity were assessed. Skeletal muscle metabolomic analysis of acylcarnitines and PGC1α mRNA expression via qRT-PCR were measured. Results Quercetin at 50 ug/day for 8 wk attenuated HFD-induced increases in fat mass, body weight and IR and increased PGC1α expression, whereas 600 ug/day of quercetin exacerbated fat mass accumulation without altering body weight, IR or PGC1α. PGC1α expression correlated with acylcarnitine levels similarly in HF and HF+600Q; these correlations were not present in HF+50Q. At both time points, energy expenditure increased in HF+50Q and decreased in HF+600Q, independent of PGC1α and IR. Conclusions/interpretation Chronic dietary quercetin supplementation at low but not higher dose ameliorates the development of diet-induced IR while increasing PGC1α expression in muscle, suggesting that skeletal muscle may be an important target for the insulin-sensitizing effects of a low dose of quercetin.